Análise geomorfológica da Bacia Hidrográfica do Rio Mearim-MA a partir do quadro geológico regional - Alex de Sousa Lima (2013)
The relief is reflective of many transformations occurred in past times, under a set of processes that intertwine and combine to result in a dynamic product apparently static. Thus, it is understood that the watershed is an ideal unit to understand how such transformations occur. Accordingly, we adopted the River Basin Mearim - MA as an object of study for understanding the dynamics of these processes acting relief. The objective of this research was to characterize and understand the geomorphological aspects of the basin based on the geological evolution of the sedimentary basin of the St. Louis-Grajaú The methodology was based on the analysis and discussion of the regional geological framework from the literature, with complementary use of tables, maps, profiles and block-diagrams drawn in order to obtain better visualization of relevant information to the forms of relief. Initially, we analyzed the characteristics hypsometric and slope, through the maps and tables, which allowed considering the river basin Mearim is in conditions where the processes of aggradation excel on the degradation of relief, especially in the lower course. Results and discussions profiles and block - diagrams indicated a differentiation between low and medium distances, as well as the eastern and western portions of the basin. Also indicated for individualization in two areas to the lower course. The morphometric analysis have revealed that there is insufficient energy to form new channels, reflecting the low slope of the basin. The sinuosity index indicates the influence of faulting due to extensive courses straight. Proposed to the evolutionary model of river basin Mearim in five stages: stage I, Albian, formation of by - draining, stage II, Campanian, activation of faulting and regressive erosion, stage III, Late Oligocene, lowering of sea level and accentuation of the erosion process, stage IV, Middle Miocene, dismantling coverage aluminous and iron - capture Grajaú river Lineament, and stage V, Plio-Pleistocene, deployment plains and differentiation of the eastern and western portions of the basin. From the results we highlight five geomorphological units, as follows: Unit I , High - Mearim Grajaú; Unit II, Relief Dissected Middle Mearim; Unit III, the Dissected Surface Pindaré; Unit IV, dissected relief of the Lower Course, and, Unit V, Plain fluviallacustrine environment and Navy. Based on the results it was found that there was neotectonics in the lower course, responsible for the configuration of the drainage and fluvial-lacustrine plains.